Pengaruh Pemanfaatan ChatGPT dan Motivasi Belajar terhadap Kemampuan Berpikir Kritis yang dimediasi oleh Perilaku Belajar Mahasiswa Universitas Negeri Padang - Alif Al Amar Nasution; Rino (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of ChatGPT usage and learning motivation on critical thinking skills, mediated by the learning behaviors of students at Padang State University. This is a causal study. The population consists of undergraduate students at Padang State University who use ChatGPT in their learning activities. The sample comprised 210 respondents, determined using Hair formula and proportional random sampling. technique Primary data were collected through the distribution of questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that the use of ChatGPT has a positive and significant effect on critical thinking skills, learning behavior, and learning motivation. Learning motivation also has a positive and significant effect on learning behavior, while learning behavior has a positive and significant effect on critical thinking skills. Furthermore, learning behavior was found to mediate the relationship between the use of ChatGPT and learning motivation on critical thinking skills, and learning motivation mediates the effect of ChatGPT use on learning behavior.